2016
DOI: 10.3389/fmicb.2016.00645
|View full text |Cite
|
Sign up to set email alerts
|

A Network of Paralogous Stress Response Transcription Factors in the Human Pathogen Candida glabrata

Abstract: The yeast Candida glabrata has become the second cause of systemic candidemia in humans. However, relatively few genome-wide studies have been conducted in this organism and our knowledge of its transcriptional regulatory network is quite limited. In the present work, we combined genome-wide chromatin immunoprecipitation (ChIP-seq), transcriptome analyses, and DNA binding motif predictions to describe the regulatory interactions of the seven Yap (Yeast AP1) transcription factors of C. glabrata. We described a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 108 publications
3
44
0
Order By: Relevance
“…These comprised mostly orthologs from the S. cerevisiae iron network, including Aft1, its functionally redundant paralog Aft2 (32), and the fungus-specific bZIP transcription factor Yap5, an intracellular iron sensor (33). C. glabrata Yap5, along with Yap7, has recently been shown to regulate iron sulfur cluster biogenesis and heme biosynthesis in a global chromatin immunoprecipitation (ChIP) and transcriptome analysis approach (34). Additionally, members of the Hap complex were tested, e.g., Hap4 and Hap5, known to contribute to Hap43-regulated iron homeostasis in C. albicans (35) but to respiratory gene expression in S. cerevisiae (36) and with an unclear role in C. glabrata .…”
Section: Resultsmentioning
confidence: 99%
“…These comprised mostly orthologs from the S. cerevisiae iron network, including Aft1, its functionally redundant paralog Aft2 (32), and the fungus-specific bZIP transcription factor Yap5, an intracellular iron sensor (33). C. glabrata Yap5, along with Yap7, has recently been shown to regulate iron sulfur cluster biogenesis and heme biosynthesis in a global chromatin immunoprecipitation (ChIP) and transcriptome analysis approach (34). Additionally, members of the Hap complex were tested, e.g., Hap4 and Hap5, known to contribute to Hap43-regulated iron homeostasis in C. albicans (35) but to respiratory gene expression in S. cerevisiae (36) and with an unclear role in C. glabrata .…”
Section: Resultsmentioning
confidence: 99%
“…Using the PathoYeastract database (http://pathoyeastract.org/cglabrata/index.php Monteiro et al, 2016), it is possible to verify that the CgFLR1 was found to be up-regulated upon the over-expression of CgPdr1, in control conditions (Noble et al, 2013), or upon benomyl or selenite exposure, in the dependency of CgYap1 (Chen et al, 2007; Lelandais et al, 2008; Merhej et al, 2016). Additionally, CgFLR1 expression was shown to be repressed by the transcription factor Stb5, a negative regulator of azole resistance in C. glabrata (Noble et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CgFLR1 expression was shown to be repressed by the transcription factor Stb5, a negative regulator of azole resistance in C. glabrata (Noble et al, 2013). Chromatine ImmunoPrecipitation (ChIP) assays further showed that Yap7 binds to the CgFLR1 promoter in selenite exposed cells (Merhej et al, 2016). Information on the regulation of CgFLR2 is much scarcer.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the query ‘Rank by TF’ was designed to accept as input a list of genes, for example, the set of genes up-regulated in a given condition, as obtained by RNA sequencing or microarray analysis, providing as output the TFs that regulate the user's gene list, ranked by relative importance. For example, a recent study on the role of the C. glabrata Yap1 TF, a master regulator of the oxidative stress response in yeasts, provided a list of 70 genes which are up-regulated in C. glabrata cells exposed to stress induced by selenium, under the control of Yap1 (27). Using the ‘Rank by TF’ query to analyse the same list, it is possible to observe that besides Yap1, 14 other TFs play a role in the regulation of this gene list, suggesting that the network of TF responsible for the transcriptional remodelling occurring in these cells is much more complex than initially foreseen (Figure 3).…”
Section: Introductionmentioning
confidence: 99%
“…Using the ‘Rank by TF’ query to analyse the same list, it is possible to observe that besides Yap1, 14 other TFs play a role in the regulation of this gene list, suggesting that the network of TF responsible for the transcriptional remodelling occurring in these cells is much more complex than initially foreseen (Figure 3). The authors of the paper describing the role of Yap1 in the C. glabrata selenium response focused on the participation of some of the Yap1 homologs (27), however, TFs such as Pdr1, Skn7 or even the uncharacterized TFs encoded by ORF CAGL0I07755g (an homologue of the salt stress related S. cerevisiae Hal9 TF) or ORF CAGL0G08844g (an homologue of the cell wall stress related S. cerevisiae Asg1 TF) also appear highly ranked in this query, as they are required for the transcriptional control of >10% of the dataset in analysis. This result appears to suggest that selenium stress induces toxicity at several levels, beyond oxidative stress, thus activating an array of TF that control various biological functions required for C. glabrata cells to cope with selenium stress.…”
Section: Introductionmentioning
confidence: 99%